2018
DOI: 10.3390/ma11101919
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Micromechanics Models for Elastoplastic Behavior of Long Fibrous Composites: A Critical Review and Comparative Study

Abstract: Elasto-plastic models for composites can be classified into three categories in terms of a length scale, i.e., macro scale, meso scale, and micro scale (micromechanics) models. In general, a so-called multi-scale model is a combination of those at various length scales with a micromechanics one as the foundation. In this paper, a critical review is made for the elastoplastic models at the micro scale, and a comparative study is carried out on most popular analytical micromechanics models for the elastoplastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 273 publications
0
29
0
Order By: Relevance
“…The transverse and shear strengths of the yarns were calculated using the bridging model constitutive theory of unidirectional composite materials, which was developed by Wang and Huang. 32 The transverse strength was assessed as follows:…”
Section: Materials Modelsmentioning
confidence: 99%
“…The transverse and shear strengths of the yarns were calculated using the bridging model constitutive theory of unidirectional composite materials, which was developed by Wang and Huang. 32 The transverse strength was assessed as follows:…”
Section: Materials Modelsmentioning
confidence: 99%
“…For example, the incremental tangent model 5 , deformation secant model 6 , incremental-secant model 7 , isotropization Eshelby tensor approach 2 , etc. A comprehensive review concerning elastoplastic models can be found in Kanouté et al 8 , Saeb et al 9 and Wang et al 10,11 However, it is reported that the predicted properties of such models are too stiff compared with experiment data 12 . Some researchers 13,14 believe that it is because such models take the elasto-plastic deformation of a matrix as the only source of nonlinearity of a composite while the contribution of interface damage is ignored.…”
Section: A Micromechanics Based Elastoplastic Damage Model For Unidirmentioning
confidence: 99%
“…(3-6) with tangent instantaneous ones, as shown in Eqs. (10)(11)(12). Parameters with superscript or subscript t denote tangent instantaneous quantities.…”
mentioning
confidence: 99%
“…Numerical modeling of ratcheting of the composites has been investigated by many researchers during the past decades [20,21,22,23,24,25]. The classical micromechanics models under the framework of the Eshelby theory [26] and the Mori–Tanaka model [20,21] were built to simulate the mechanical response of metal matrix composites.…”
Section: Introductionmentioning
confidence: 99%